Fabrication and characterization of polyetherimide/polyvinyl acetate polymer blend membranes for CO2/CH4 separation - Abdul Mannan, H. (2019)
This article presents fabrication, characterization, and performance evaluation of polyetherimide (PEI)/polyvinyl acetate (PVAc) blend membranes. Polymer blend membranes with various blend ratios of PEI/PVAc were prepared by solution casting and evaporation technique. Morphology and miscibility of polymer blend membranes were characterized by field emission scanning electron microscope (FESEM) and differential scanning calorimetry (DSC), respectively. The interaction between blend polymers was analyzed by FTIR analysis. Gas separation performance was evaluated in terms of permeability and selectivity. FESEM results revealed that pure polymer and blend membranes were homogeneous and dense in structure. A single glass transition temperature of polymer blend membranes was found in DSC analysis which indicated the miscibility of PEI/PVAc blend. FTIR analysis confirmed the presence of molecular interaction between blend polymers. The permeation results showed that the presence of PVAc (3 wt) in blend membranes has improved CO2 permeability up to 95 compared to pure PEI membrane. In addition, CO2/CH4 selectivity was found to be 40 higher than pure PEI membrane. This study shows that blending a small fraction of PVAc can improve the gas separation performance of PEI/PVAc blend membranes. POLYM. ENG. SCI., 59:E293âE301, 2019. Â© 2018 Society of Plastics Engineers. Â© 2018 Society of Plastics Engineers